Sustentabilidade e Ambientalização na Universidade Federal de Uberlândia - Santos, Mariana Moreira (2023)
Considering the current environmental crisis, it is a support for universities to adopt horizontal measures regarding sustainability in everyday life and in the practice of their campuses, including commitment and engagement of professionals and students involved; added to the strengthening of research, teaching and extension initiatives aimed at proposing improvements and repairs in the environmental perspective, both for the locations where they host, and for society itself. This research is a Dissertation of the Master's Course of the Graduate Program in Geography (PPGEO) of the Institute of Geography (IG) of the Federal University of Uberlândia (UFU), in the line of research III: Geographical Education and Social Representations, which has as a general objective to understand the insertion of the environmental theme in the Federal University of Uberlândia (UFU) and the curricular environmentalization in the UFU campuses in Uberlândia. A bibliographical review was carried out on the themes Sustainability, Sustainable Development, Sustainable Universities, Environmental Education and Curricular Environmentalization, the investigation of the existence of environmental measures and practices in the UFU and analysis of the disciplines related to the environmental theme offered in the development courses of the UFU. Among the results obtained, it was found that the panorama of environmentalization of the UFU is positive - the UFU is on the path of EE and sustainable development. However, curricular environmentalization in initiation courses is a point that should be looked at with more caution – it is necessary to include obligatory environmentalized disciplines in all courses. The formation of qualified professionals and the production of knowledge and environmental knowledge are essential factors for the transformation of reality and the construction of new paradigms.